2022
DOI: 10.3390/foods11182739
|View full text |Cite
|
Sign up to set email alerts
|

Actinidin in Green and SunGold Kiwifruit Improves Digestion of Alternative Proteins—An In Vitro Investigation

Abstract: Both Hayward (green) and SunGold (gold) kiwifruit varieties contain a proteolytic enzyme, actinidin, that has been reported to enhance the upper tract digestion of animal proteins. Unlike the other gold varieties, which do not contain any actinidin, the SunGold variety contains significantly higher actinidin activity, but its activity is still much lower than that present in the green (Hayward) fruit. The objective of this study was to determine the effectiveness of actinidin in Hayward and SunGold kiwifruit i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…We determined that GRJ (38.05±1.08) had a higher protease activity than GOJ (30.13±2.95) (p<0.05). This result was consistent with the previous study that green kiwifruit had a higher specific protease activity than gold kiwifruit [18]. Chao [19] reported that actinidin content determined protease activity even among kiwifruit species with similar protein concentrations.…”
Section: Protease Activities Of the Green And Gold Kiwifruit Juicessupporting
confidence: 93%
“…We determined that GRJ (38.05±1.08) had a higher protease activity than GOJ (30.13±2.95) (p<0.05). This result was consistent with the previous study that green kiwifruit had a higher specific protease activity than gold kiwifruit [18]. Chao [19] reported that actinidin content determined protease activity even among kiwifruit species with similar protein concentrations.…”
Section: Protease Activities Of the Green And Gold Kiwifruit Juicessupporting
confidence: 93%
“…The results for the first time indicate that both SunGold and Hayward kiwifruit can improve the breakdown and digestion of other proteins when eaten as part of a meal. As a result, they have the potential to be used as a digestive aid in populations like athletes, the elderly, and those with impaired digestive systems who want to achieve faster and greater protein digestion [28] .…”
Section: Lovedeep Kaur Et Al (2022)mentioning
confidence: 99%
“…It is important to note that there is a large interindividual difference in response to enzyme preparations [32], which requires a more detailed study in the future of the optimal response to enzyme replacement therapy among different population categories. In particular, there is potential for the use of actinidin as a beneficial factor to improve and accelerate the protein digestion process among certain groups of people -athletes, the elderly, and people with digestive organ pathology [33].…”
Section: огляди літератури / Literature Reviewsmentioning
confidence: 99%